CRYOPRESERVATION OF SHOOT TIPS AND POLLEN OF POTATO - Smyda-Dajmund, Paulina (Plant Breeding and Seed Science, 2017)
Cryopreservation is a frequently used method of long-term storage of potato meristems and pollen in liq-uid nitrogen (LN) in temperature of -196°C. This technique allows for theoretically unlimited storage of pota-to material. The most popular method of potato shoot tips preservation is cryopreservation by the solidifica-tion of liquids without crystallization (vitrification).The best method of pollen conservation is its direct im-mersion in LN. The successful regeneration after vitrification is genotype-dependent, which require optimiza-tion of protocol.